Female engagement in STEM through hybrid programs (Ireland TUD-model) - Ramirez, Claudia Patricia Ovalle (Frontiers in Education, 2025)
PurposeThe article describes factors that may boost female participation in STEM undergraduate programs and a model applied at TUD (Technical University Dublin).Design/methodology/approachIt presents a case study in Higher Education involving an ecosystem that fosters the involvement of females in one STEM hybrid undergraduate program in Ireland.FindingsThe successful program implemented by TUD was based on empirical research that demonstrates that females do not lack skills but have a diverse profile of abilities. Therefore, females need undergraduate hybrid programs designed to attract them and develop their multiple skills, involving not only Engineering but also practical training in fields such as Medicine, Management and World Languages.ConclusionThe “Infrastructures of Inclusion” such as hybrid programs and high impact practices (academic, social, institutional), are relevant for involving a higher proportion of females in STEM fields such as Computer Science.Practical implicationsFuture research may evaluate the impact of hybrid programs in STEM to boost female participation in other countries.Research limitationsThe research is limited to one geographical area (Dublin, Ireland).Originality/valueThis article contributes to inform interested researchers with one model hosted at TUD Dublin.